Factors Influencing Quality of Life and Functional Outcomes in Patients With Bladder Cancer - Qing Zhou; Xi Chen; Qiuyan Chen; Lu Hao (Cancer Control, 2023)
Here, we review the quality of life and functional outcomes of patients with bladder cancer after treatment and assess potential contributing factors. For current scoring systems, we highlighted the most commonly used specificity scores. In addition, we discuss the impact and bias on the quality of life of patients undergoing urinary diversion modalities, robotic surgery, perioperative rehabilitation, and bladder-preserving radiochemotherapy. Through this review, clinicians will gain better insights regarding the importance of improving patients' quality of life with the goal of restoring their patients’ normal function and participating in social activities.